ANALISIS PERBEDAAN RETURN SAHAM DAN LIKUIDITAS SAHAM STOCK SPLIT (Studi Kasus pada Perusahaan yang Melakukan Stock Split di Bursa Efek Indonesia periode 2016-2018) - Anni Muthmainnah Amaliyah; Wiwin Aminah (SOSIOHUMANITAS, 2020)
The capital market is a means used by companies to obtain additional funds by trading shares to investors. Stock prices that are too high will make investors reluctant to invest. This is what drives companies to carry out corporate action activities in the form of stock splits. Stock splitting aims to break down a sheet of shares into smaller ones so that stock prices can be more affordable for investors.This study aims to look at the comparison of stock returns by making abnormal returns a measuring tool and trading volume activity for stock liquidity before and after stock splits. The phenomenon in this study was explored by the event study method, using secondary data. The observation period was 10 days before, one day at the time, and 10 days after the stock split. There were 42 companies that conduct stock splits for the 2016-2018period and at the same time were the samples in this study. The hypothesis testing used was the Wilcoxon Signed-Rank Test with a significance level (α) of 5% and analyzed using SPSS 25.00 software. Stock returns have a significant difference, while stock liquidity does not have a significant difference before and after a stock split. The results of this study are expected to be one of the decision-making tools for investors. In addition, this research can be used as a direction for companies to be careful in carrying out stock split activities.